Pengaruh Brand Awareness, Distribusi Produk, dan Harga Terhadap Keputusan Pembelian Cairan Kimia Otomotif Kalangan Pengguna Mobil: (Studi Kasus Pelanggan CV. Devika Jaya Group Area Yogyakarta dan Semarang) - Aryanto Purbantoro; Pemillia Sulistyowati (LPPM Politeknik Pratama, 2026)
This study aims to determine the influence of brand awareness, product distribution, and price on purchasing decisions for automotive chemical fluids among customers of CV. Devika Jaya Group in Yogyakarta and Semarang. The study used a quantitative approach with a survey technique using a questionnaire to 100 respondents. Data were analyzed using multiple linear regression using SPSS 26. The results indicate that partially, brand awareness, product distribution, and price have a positive and significant influence on purchasing decisions. Price has the most dominant influence, followed by product distribution and brand awareness. Simultaneously, these three variables explain 72.7% of the variation in purchasing decisions, while the remaining 27.3% is influenced by factors outside the research model. These findings confirm that an effective marketing strategy depends not only on competitive pricing but also on brand awareness and effective product distribution.